“I didn't know you could do that”: A Pilot Assessment of EHR Optimization Training - Gold, Rachel; Bunce, Arwen; Davis, James V.; Nelson, Joan C.; Cowburn, Stuart; Oakley, Jee; Carney, Stacie; Horberg, Michael A.; Dearing, James W.; Melgar, Gerardo; Bulkley, Joanna E.; Seabrook, Janet; Cloutier, Heath (ACI Open, 2021)
Background Informatics tools within electronic health records (EHRs)—for example, data rosters and clinical reminders—can help disseminate care guidelines into clinical practice. Such tools' adoption varies widely, however, possibly because many primary care providers receive minimal training in even basic EHR functions.Objectives This mixed-methods evaluation of a pilot training program sought to identify factors to consider when providing EHR use optimization training in community health centers (CHCs) as a step toward supporting CHC providers' adoption of EHR tools.Methods In spring 2018, we offered 10 CHCs a 2-day, 16-hour training in EHR use optimization, provided by clinician trainers, and customized to each CHC's needs. We surveyed trainees pre- and immediately post-training and again 3 months later. We conducted post-training interviews with selected clinic staff, and conducted a focus group with the trainers, to assess satisfaction with the training, and perceptions of how it impacted subsequent EHR use.Results Six CHCs accepted and received the training; 122 clinic staff members registered to attend, and most who completed the post-training survey reported high satisfaction. Three months post-training, 80% of survey respondents said the training had changed their daily EHR use somewhat or significantly.Conclusion Factors to consider when planning EHR use optimization training in CHCs include: CHCs may face barriers to taking part in such training; it may be necessary to customize training to a given clinic's needs and to different trainees' clinic roles; identifying trainees' skill level a priori would help but is challenging; in-person training may be preferable; and inclusion of a practice coach may be helpful. Additional research is needed to identify how to provide such training most effectively.
Keywords: electronic health records; community health centers; safety-net providers; education; professional; retraining